Climate modelling for agroforestry species selection in Yunnan Province, China. (January 2016) - Ranjitkar, Sailesh; Sujakhu, Nani Maiya; Lu, Yang; Wang, Qing; Wang, Mingcheng; He, Jun; Mortimer, Peter E.; Xu, Jianchu; Kindt, Roeland; Zomer, Robert J.
Abstract: Changing climate is likely to impact on both tree species and agroforestry systems in a variety of ways. A multi-model ensemble approach based on ecological niche modelling was used to understand the impact of climate on distribution of agroforestry trees in Yunnan Province of China. Future changes in distribution of 10 agroforestry tree species were projected using an ensemble of climate projections derived from the results of 19 Earth System Models provided by the Coupled Model Inter-comparison Project-Phase 5. Our model explained suitable habitat, and identified potential locations for mixed agroforestry using selected species. The model suggested west and southwest Yunnan as important location for tea and alder-based agroforestry, while southern parts of Yunnan are better suited for tea and hog plum, and northern parts could support walnut-based agroforestry options. Agroforestry is an important adaptation option for climate change, which could benefiting farmers and enhancing environmental conservation and restoration of the landscape. Graphical abstract: Highlights: The ensemble model shows where we are most certain that the species is suitable. The tuning procedure with weighted AUC chose a specific number of best models for ensemble. Based on sensitivity analysis of spatially nested predictions where all sub-models agree that the species is suitable. A multi-model ensemble approach identified suitable habitat for agroforestry tree species. Mixed agroforestry choices for future climate recommended using consensus map outputs.